Rv1458c: a new diagnostic marker for identification ofMycobacterium tuberculosiscomplex in a novel duplex PCR assay. Issue 3 (March 2017) - Shrivastava, Kamal; Garima, Kushal; Narang, Anshika; Bhattacharyya, Kausik; Vishnoi, Ekta; Singh, Roshan Kumar; Chaudhry, Anil; Prasad, Rajendra; Bose, Mridula; Varma‐Basil, Mandira
Abstract : Purpose. : We explored the efficiency of Rv1458c, the gene encoding a putative ABC drug transporter specific for the Mycobacterium tuberculosis complex (MTBC), as a diagnostic marker. Methodology. : A 190 bp region of Rv1458c and a 300 bp region of hsp65 were targeted in a novel duplex PCR assay and the results were compared with those for PCR restriction analysis(PRA) using the restriction enzymes NruI and BamHI. Species identification of a subset of the isolates ( n =50) was confirmed by sequencing. Clinical isolates of M. tuberculosis ( n =426) obtained from clinically suspected patients of pulmonary tuberculosis and mycobacterial ( n =13) and non‐mycobacterial ( n =8) reference strains were included in the study. Results. : The duplex PCR assay correctly identified 320/426 isolates as MTBC and 106/426 isolates as non‐tuberculous mycobacteria(NTM). The test was 100% specific and sensitive when compared with NruI/BamHI PCR restriction analysis and highlighted the use of Rv1458c as a diagnostic marker for MTBC. Conclusion. : The duplex PCR assay could be developed for use as a screening test to identify MTBC in clinical specimens in peripheral laboratories with limited resources.